Analisis Hukum Islam Terhadap Praktek Jual Beli Gabah Hasil Pertanian Pada Pedagang (Studi Kasus Di Desa Kulo Kecamatan Kulo Kabupaten Sidenreng Rappang) - Ridwan Senong; Muliati; Suarning (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2024)
This research aims to explore the analysis of Islamic law related to the practice of buying and selling agricultural grain between farmers and traders, which is often carried out in large quantities using a weighing system that is vulnerable to dishonesty and fraud. The focus of this research is on the action of unilaterally setting the weighing equipment by the trader as well as cutting the weight of the scale per sack of grain after weighing it. The research method used is field research with a descriptive qualitative nature and an empirical juridical approach, with primary data from direct interviews and secondary data from Islamic literature such as the Al-Qur'an, hadith, books and online print media. The research results show that the practice of buying and selling grain is carried out with various agreements at the farmer's house or at the location where the grain is stored, however factors such as a lack of understanding of Islamic legal rules, limited sales alternatives, and cultural factors also encourage people to continue this practice. According to Islamic law, this practice is considered unacceptable because it violates the principle of dishonesty and is detrimental to farmers.